Failure criteria in fibre reinforced polymer composites the World-Wide Failure Exercise - Hinton, M. J. (Mike J.); Kaddour, A. S.; Soden, P.D
Providing vital information on all the latest theories predicting failure in fiber reinforced polymer composites.